Strength of Onyx-based composite 3D printing materials according to fiber reinforcement - Lee, Gyu-Wol; Kim, Tae-Hyun; Yun, Jong-Hwan; Kim, Nam-Joo; Ahn, Ki-Hwan; Kang, Min-Soo (Frontiers in Materials, 2023)
This study evaluates the mechanical strength of 3D-printed objects of composite material. The composite material considered in this study comprises onyx as the base material with glass fiber and carbon fiber as the internal reinforcements. 3D printing using composite materials generally involves laminating fiber reinforcements in the form of layers within the printed part. To analyze the effect of such reinforcements on the printed parts, specimens were prepared by varying the number of layers and arrangement conditions of the reinforcement. The analysis shows that the tensile strength of the composite increases with the number of reinforcement layers due to the effect of the fibers on the longitudinal direction and a larger bonding area between the internal Onyx and the fibers. Furthermore, higher tensile strength is observed when the reinforcements are laminated at regular intervals than when they are arranged in the center. This study serves as a database for 3D printing fiber-reinforced composites aiding future research in comparing and optimizing their strength according to the 3D printing conditions.